Are German stock and bond returns consistent with equilibrium asset pricing? A calibration exercise using recursive non-expected utility - Bernd Meyer (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
This paper reexamines the Equity Premium Puzzle for the German stock market with control for inflation and taxation. Two methods for relaxing the assumption of aggregate consumption being equal to aggregate dividends are compared: the leverage approach and the usage of a bivariate stochastic process. Markov mixtures of univariate and bivariate normal distributions for the stochastic processes of consumption and dividends are estimated directly from the data and evaluated by Monte Carlo simulations. Preferences are modeled by time-additive expected utility and, alternatively, by recursive non-expected utility. The empirical results for the period 1960 to 1994 confirm those for the U.S. and favour the use of recursive non-expected utility which clearly distinguishes between risk preference and time preference. The leverage approach yields the first moment of the risk-free rate and the first and second moments of the risk premium on the stock market with plausible preference parameters. The bivariate approach yields smaller risk premia because the assumption of perfect correlation between consumption and dividends is relaxed; the correlation is equal to the low value historically observed, reducing the risk premia in comparison with the leverage approach.
Keywords: 330; Kapitaleinkommen; Börsenkurs; Risikoprämie; Erwartungstheorie; Nutzen; Gleichgewichtstheorie; Deutschland; Theorie